2021
DOI: 10.15537/smj.2021.42.5.20200422
|View full text |Cite
|
Sign up to set email alerts
|

The association between diabetes numeracy and diabetes self-management among Saudi adults with insulin-treated diabetes

Abstract: Objectives: To describe the association between diabetes numeracy and diabetes self-management among Saudi adults with insulin-treated diabetes. Methods: From August 2018 to January 2019, a cross-sectional study was conducted in 3 diabetes centers in Riyadh, Buraydah, and Jeddah, Saudi Arabia. Systematic random sampling was used to include 290 Saudi adults with insulin-treated diabetes. The levels of diabetes numeracy and diabetes self-management were measured by using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…Furthermore, lifestyle changes, including diet and exercise, can lead to a reduction in hemoglobin A1C of up to 2% [ 51 , 52 ]. The dietary control scores reported in this study were the highest reported in KSA and higher than post-COVID-19 scores in Turkey [ 16 , 17 , 43 , 45 , 46 ]. The only exception was the dietary scores reported in healthcare providers; however, this population was different than our study and it is expected that healthcare professionals dealing with patients with diabetes would have better dietary control, due to more knowledge about the dietary recommendations and to access to healthier food choices [ 44 ].…”
Section: Discussionmentioning
confidence: 61%
See 3 more Smart Citations
“…Furthermore, lifestyle changes, including diet and exercise, can lead to a reduction in hemoglobin A1C of up to 2% [ 51 , 52 ]. The dietary control scores reported in this study were the highest reported in KSA and higher than post-COVID-19 scores in Turkey [ 16 , 17 , 43 , 45 , 46 ]. The only exception was the dietary scores reported in healthcare providers; however, this population was different than our study and it is expected that healthcare professionals dealing with patients with diabetes would have better dietary control, due to more knowledge about the dietary recommendations and to access to healthier food choices [ 44 ].…”
Section: Discussionmentioning
confidence: 61%
“…In the current study, participants reported high glucose management scores. Two studies in similar patient populations to this study had slightly higher scores in this domain and one had lower scores, but it appears as the COVID-19 pandemic did not lead to significant changes in glycemic management [ 16 , 45 , 46 ]. This was directly expressed by the study participants in their answers to the three COVID-19 questions.…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…It is important to note that participants who intended to make lifestyle modifications had higher numeracy skills. The desire for self-management has been previously demonstrated to be positively correlated with DNT-15 [ 80 ]. Given the chronicity of diabetes, it is fundamental for individuals to be motivated to tackle the challenging aspects of the disease.…”
Section: Discussionmentioning
confidence: 99%